Upaya Peningkatan Keragaman Kedelai Kipas Merah Melalui Iridiasi Sinar Gamma - Zuyasna Zuyasna; Chairunnas Chairunnas; Efendi Efendi; Arwin Arwin (Universitas Teuku Umar, 2022)
Plant genetic diversity has an important meaning in plant breeding programs. High genetic diversity allows breeders to select plant genotypes according to the desired breeding objectives. One of the efforts to increase diversity is through mutation induction techniques. Research has been carried out to increase the diversity of Kipas Putih soybeans by using gamma ray irradiation. Radiation was carried out on Kipas Putih soybean seeds as a result of pure strain selection using an irradiation level of 100-1000 Gy in Batan. The pure Kipas Putih line that has been irradiated, is planted on dry land according to the technical instructions for soybean cultivation and allowed to self-pollinate. Furthermore, after physiological maturity, the seeds were harvested and dried to obtain the Aceh succession M1 seed population. All the growing mutant plants were evaluated for morphological characteristics and yields. The results showed that the highest diversity was at the irradiation level of 200-300 Gy. Gamma ray irradiation can induce genetic diversity of Kipas Putih soybean which is indicated by variations in stem shape, leaf and yield. The higher the level of irradiation, the higher the level of cell and tissue damage, even resulting in death. The first generation mutant (M1) Kipas Putih soybean has the potential to produce a line with a higher yield than the original plant and allows selection of new characters such as drought tolerance, disease resistance, and high yield. It is necessary to select the M2, M3, and M4 generations on selected lines for drought tolerant characters and high production.